The role of tribbles homolog 2 in cell proliferation - Wenkang Zhang; Mingkang Li; Minhao Zhang; Gaoliang Yan; Chengchun Tang (Cell Communication and Signaling)
Abstract Tribbles homolog 2 (TRIB2), a pseudoserine/threonine kinase, is a member of the TRIB family. TRIB2 primarily regulates cell proliferation through its scaffold or adaptor effect on promoting the degradation of target proteins by E3 ligase-dependent ubiquitination and regulating mitogen-activated protein kinase (MAPK) and protein kinase B (AKT) signaling pathways. TRIB2 is not only involved in the physiological proliferation of cells (granulosa cells, myoblasts, naive T cells, and thymocytes) during normal development but also in the pathological proliferation of vascular smooth muscle cells and a variety of cancer cells (lung cancer cells, liver cancer cells, leukemia cells, pancreatic cancer cells, gastric cancer cells, prostate cancer cells, thyroid cancer cells, cervical cancer cells, melanoma cells, colorectal cancer cells, ovarian cancer cells and osteosarcoma cells) under disease conditions. Its expression level and functional role predominantly hinge on the specific tissue and cell type it targets. This review elucidates the specific mechanisms of TRIB2 in physiological and pathological cell proliferation from the perspective of different kinds of cells.